Independent task system to develop communicative competence in English with medical purpose. - Belkys Gonzalez Machin; Juana I. Hernández Fernández; Edita Solano López; Julio Peraza Vargas (Medisur)
Differentiated taks system constitutes a methodological strategy in the teaching of English with medical purposes through systemic activities using the English native students of the 4th year of medicine specialty. This observational, analytic, comparative study was performed with 90 students taken from 5 groups which constituted the universe of this investigation. Each group of students by itself constituted an independent sample integrated in a fair way by native students of the English speaking countries, Spanish speaking countries and any other. This system permitted the achievement of communicative competences through an approach to the communicative knowledge of the students in their classroom interaction. Four macro habilities of the English language were developed, and the management of the language sub system was improved. An adequate preparation for future missions abroad in their labor field was obtained.